KONVEYOR PORTABLE PEMUAT TANDAN BUAH SEGAR (TBS) KELAPA SAWIT KE KENDARAAN PENGANGKUT - Zoel Fachri; Muhammad Muslem (J-Innovation, 2020)
The process of sorting oil palm fresh fruit bunches in the loading ramp is carried out by male operators in the form ofactivities to reduce and raise oil palm bunches to trucks with the weight of oil palm bunches ranging from 20 kg to 25 kgusing a corner. workers have to manually raise oil palm bunches by piercing oil palm fruits and raising them into truckscausing operators to complain of muscle pain (MSDs), the complaints experienced by operators are increasing in proportionto the number of trucks that must be loaded or unloaded. So from the above problems the authors make a new innovationthat is Portable Oil Palm Bunch Loader Conveyor into the Transport Vehicle. The palm oil bunch loader loader is poweredby a DC motor with a 12 volt voltage, the source of energy from car battery batteries that are on site. On this conveyor thereare 2 legs (pedestal) front and back, the height of the rear legs 50 cm (fixed) and the front legs can be set at a height of 100cm (slope 9̊) and a height of 140 cm (slope 14̊), at a height of 100 cm with a load of 46 kg voltage of 12.03 Volts, current134.0 mA, motor speed of 5.4 rpm and at an altitude of 140 cm with a load of 46 kg voltage of 12.03 Volts, current of 151.4mA, motor speed of 5.4 rpm. From the results of testing the conveyor is able to transport oil palm up to a weight of 46 kginto a transport vehicle in one charge.